Experimental Study and Numerical Solution of Poly Acrylic Acid Supported Magnetite Nanoparticles Transport in a One-Dimensional Porous Media - M. Golzar; S. F. Saghravani; M. Azhdari Moghaddam (Advances in Materials Science and Engineering)
Recently, iron nanoparticles have attracted more attention for groundwater remediation due to its potential to reduce subsurface contaminants such as PCBs, chlorinated solvents, and heavy metals. The magnetic properties of iron nanoparticles cause to attach to each other and form bigger colloid particles of iron nanoparticles with more rapid sedimentation rate in aqueous environment. Using the surfactants such as poly acrylic acid (PAA) prevents iron nanoparticles from forming large flocs that may cause sedimentation and so increases transport distance of the nanoparticles. In this study, the transport of iron oxide nanoparticles (Fe3O4) stabilized with PAA in a one-dimensional porous media (column) was investigated. The slurries with concentrations of 20,100 and 500 (mg/L) were injected into the bottom of the column under hydraulic gradients of 0.125, 0.375, and 0.625. The results obtained from experiments were compared with the results obtained from numerical solution of advection-dispersion equation based on the classical colloid filtration theory (CFT). The experimental and simulated breakthrough curves showed that CFT is able to predict the transport and fate of iron oxide nanoparticles stabilized with PAA (up to concentration 500 ppm) in a porous media.